Propuesta de articulación de servicios ecosistémicos basado en estrategias de reorganización territorial en el municipio del Agrado (Huila) - Vargas Pérez, Juan Sebastián (Universidad Antonio Nariño, 2023)
Ecosystem services are a fundamental factor for the supply of inputs necessary for the productive, economic and tourism development of a territory; this premise was altered in the particular case of the construction of the El Quimbo hydroelectric megaproje ct; the project developed below aims to make a proposal for the articulation of ecosystem services based on territorial reorganization strategies in the municipality of comprises an analytical projective research fro e l Agrado (Huila); the methodology used m a macro departmental scale approach, meso in the municipalities of influence and micro with the municipality of AgradoHuila, for its development three objectives were established which include the evaluation of territorial affectations from a timeline, the diagnosis and formulation of territorial strategies of organization and consolidation in accordance with the strengthening of the articulations of ecosystem services through the use of planning tools and instruments; the results showed the development of residential approach, protection area, bis housing areas, agroof strategies silvopastoral area, ditch protection and silvopastoral area, the study concludes that the integration of these as a basis for territorial development guarantee a positive dynam of the project ic for the recovery and activation of the area of influence